Use of Internal Structural Steel Strip Bands as Shear Reinforcement in Concrete Beams - Ahmed, Salma Nasser Korany Megahed (2017)
A Master of Science thesis in Civil Engineering by Salma Nasser Korany Megahed Ahmed entitled, "Use of Internal Structural Steel Strip Bands as Shear Reinforcement in Concrete Beams," submitted in December 2017. Thesis advisor is Dr. Sami Tabsh. Soft and hard copy available.